Bringing Microscopy-By-Sequencing into View. Issue 2 (February 2020) - Boulgakov, Alexander A.; Ellington, Andrew D.; Marcotte, Edward M.
Abstract : The spatial distribution of molecules and cells is fundamental to understanding biological systems. Traditionally, microscopies based on electromagnetic waves such as visible light have been used to localize cellular components by direct visualization. However, these techniques suffer from limitations of transmissibility and throughput. Complementary to optical approaches, biochemical techniques such as crosslinking can colocalize molecules without suffering the same limitations. However, biochemical approaches are often unable to combine individual colocalizations into a map across entire cells or tissues. Microscopy-by-sequencing techniques aim to biochemically colocalize DNA-barcoded molecules and, by tracking their thus unique identities, reconcile all colocalizations into a global spatial map. Here, we review this new field and discuss its enormous potential to answer a broad spectrum of questions. Highlights: DNA microscopy computationally can already recover spatial positions for thousands, potentially millions, or billions in the future, of molecules via sequencing. DNA microscopy sidesteps some of the limitations of optical microscopy; in principle, it can spatially locate molecules across a broad range of experimental contexts. The large extant toolbox for DNA manipulation allows for many diverse strategies and various applications. The strengths of DNA microscopy are complementary to extant biochemical and optical localization approaches and may help break new ground in fields such as brain connectomics and developmental biology.